Microbial population and nutritional compounds in the organs of tanzania-grass before and after ensilage - Zanine, Anderson de Moura; Santos, Edson Mauro; Ferreira, Daniele de Jesus; Pereira, Odilon Gomes (Semina: Ciências Agrárias, 2007)
This experiment was carried with the objective of evaluating the microbial populations and the nutritional value of different organs of plants of the tanzânia-grass (Panicum maximum) before and after the ensilage. Ten samples were collected at random at the pasture with the use of a square of 1 m2, were taken the botanical separation of the leaves in expansion, expanded leaves, leaves senesce, stem and the plant. Counting of microorganisms and the nutritional value were made in the different organs of the plant. Was determined the number of lactic bacterium, enterobacterium, fungi and yeasts and dry matter values, crude protein, neutral detergent fiber, acid detergent fiber and hemicellulose. The microbial populations were variable in function of the organ of the plant, and the stem is the organ that assures the growth of lactic bacteria and inhibition of growth of undesirable microorganisms during the ensilage of the tanzânia- grass. In the nutritional extent, a decreasing hierarchy of the value bromatológic exists: leafs in expansion, expanded leaf, plant completes and stem before and after the ensilage process.